SOSIALISASI DAN EDUKASI PENCEGAHAN COVID-19 PADA ANAK USIA SEKOLAH DI TPA NOOR IMAN, SUNGAI BESAR, BANJARBARU SELATAN, KOTA BANJARBARU - Nurul Mardiati; Muhammad Reza Pahlevi; Atni Primanadini (Jurnal Bakti untuk Negeri, 2021)
The coronavirus pandemic (COVID-19) has been declared a public health emergency or extraordinary event (KLB) and has spread to many countries and regions. The consequences of the COVID-19 pandemic are enormous and are felt by everyone around the world, including children who are growing and developing. In the Coronavirus Disease 2019 pandemic situation, which is abbreviated as COVID-19, every child without exception has the right to receive rights, protection, and clear information about the prevention and transmission of COVID-19. "Socialization and Education of COVID-19 Prevention for School-Age Children at TPA Noor Iman" is a health promotion activity for the movement of wearing masks, washing hands, and keeping a distance (3M) to prevent transmission of COVID-19. This community service activity was carried out at TPA Noor Iman Sungai Besar, Banjarbaru, South Kalimantan. This program is expected to become a medium to increase students' knowledge so that they can better understand COVID-19. Another goal, students can properly practice how to use masks and wash their hands according to WHO standards. This Community Service activity was carried out by filling in material about the causes, symptoms, and ways to prevent COVID-19. The media used are PowerPoints, videos, and props for dolls made of used socks and singing the COVID-19 jingle, which is a composition of the Rainbow song - familiar with children's daily lives. Furthermore, the children were also educated to properly practice how to use masks and wash their hands according to WHO standards. In the final session, the students who seemed to be the most active during the implementation of the program were then used as little ambassadors for COVID-19